Peningkatan Kualitas Pendidikan Jasmani sebagai Upaya Membangun Generasi Sehat di Kelurahan Pematang Gubernur dalam Kuliah Kerja Nyata Tematik - Hakim, Arif Rahman; Andri Gunawan; Ghalil Setiawan; Lasdi Arman; Nova Sabania; Putra, Dwingki Marta; Asnawati; Martiani (Jurnal Pengabdian Mitra Persada, 2025)
Healthy lifestyles in children is a global issue, and this research aims to address it through innovation. This KKN Thematic programme focuses on empowering the Pematang Governor Village community to improve the quality of physical education. By involving various parties, such as schools, local government, and the community, the programme aims to create an environment that supports students' physical activity. The first objective is to evaluate the effectiveness of new programs in increasing young people's physical activity, health and well- being. The research will identify and analyze innovative approaches in school and community contexts to increase student participation in physical activity. The research will also focus on curriculum development, the use of technology in learning, and collaboration with various stakeholders such as teachers, parents, and community leaders. Comprehensive research methods will investigate changes in physical activity before and after the program. The aim of this research is to find out how a new fitness exercise program in Pematang Governor Village can help create a healthy generation. The research will look at different new ideas that can be used in schools and community settings to increase student participation and interest in physical activity. In addition, the research will also look at how these innovations impact the physical, mental and social health of students.